2017
DOI: 10.3390/s17122848
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Transmission through Existing Building Enclosures: Destructive Monitoring in Intermediate Layers versus Non-Destructive Monitoring with Sensors on Surfaces

Abstract: Opaque enclosures of buildings play an essential role in the level of comfort experienced indoors and annual energy demand. The impact of solar radiation and thermal inertia of the materials that make up the multi-layer enclosures substantially modify thermal transmittance behaviour of the enclosures. This dynamic form of heat transfer, additionally affected by indoor HVAC systems, has a substantial effect on the parameters that define comfort. It also has an impact on energy demand within a daily cycle as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…The two domains of evaluation of the house's energy demand are linked to the materials used as well as the technical characteristics of the enclosures, although they are of a very different nature. Evaluating the actual heat flow through the enclosures throughout the year's entire cycle is a complex matter [36]. This evaluation requires simulation models that take into account construction faults, the impact of thermal inertia, real thermal bridges, as well as the incidence of solar radiation on the exterior surfaces and the air conditioning systems used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two domains of evaluation of the house's energy demand are linked to the materials used as well as the technical characteristics of the enclosures, although they are of a very different nature. Evaluating the actual heat flow through the enclosures throughout the year's entire cycle is a complex matter [36]. This evaluation requires simulation models that take into account construction faults, the impact of thermal inertia, real thermal bridges, as well as the incidence of solar radiation on the exterior surfaces and the air conditioning systems used.…”
Section: Methodsmentioning
confidence: 99%
“…Evaluating the actual heat flow through the enclosures throughout the year's entire cycle is a complex 264 matter [36]. This evaluation requires simulation models that take into account construction faults, the 265 impact of thermal inertia, real thermal bridges, as well as the incidence of solar radiation on the 266 Figure 5.…”
mentioning
confidence: 99%
“…The system creates a continuous barrier that protects the thermal envelope and prevents thermal bridges that cause energy losses in the building. This type of façade enables reducing energy demands and improving comfort levels [9]. Due to its characteristics, the system has also gained importance in parts of southern Europe such as Alicante.…”
Section: Ventilated Façadementioning
confidence: 99%
“…Several studies have demonstrated how radiant floor heating and passive cooling by convection using energy storage systems based on PCMs function correctly in the construction field [9]. Results obtained by researchers on PCMs in a Mediterranean environment led us to opt for inorganic hydrated salts as they are inexpensive and offer a large heat storage capacity per volume unit [8].…”
Section: Final Considerations Regarding Pcmsmentioning
confidence: 99%
See 1 more Smart Citation